Acute and transitional care or rehabilitation? Retrospective analysis of discharge planning from a municipal hospital in Switzerland - Lara Kollbrunner; Michael Rost; Insa Koné; Bettina Zimmermann; Yvonne Padrutt; Tenzin Wangmo; Bernice Elger (BMC, 2020)
Abstract Background Due to rising health care costs, in 2012 Switzerland introduced SwissDRG, a reimbursement system for hospitals based on lump sum per case. To circumvent possible negative consequences like reduction in length of stay, acute and transitional care (ATC) was anchored into the law (Federal act on health insurance) in 2011. ATC as a discharge option is applicable to patients who physicians deem will not fulfill rehabilitation criteria, but are unable to return home and are in need of temporary professional nursing care. ATC is associated with higher out of pocket costs to the patient than rehabilitation. Since social service workers are responsible for organizing discharge for patients with ongoing care needs after hospitalization, the aim of this study was to investigate how social service workers manage patient discharge in light of the new discharge option ATC. Methods Data was collected from 423 medical records of inpatients from Zurich's municipal hospital, Triemli, discharged to ATC or rehabilitation, in 2016. We compared the two groups using inferential statistics and qualitatively analyzed written statements from social service workers. Results Our results showed that patients discharged to rehabilitation had a higher total number of discussions, but a shorter duration of discussions. Patients discharged to rehabilitation faced more delays, mainly due to unavailability of beds in rehabilitation centers. Conflicts concerning discharge arose mainly because of costs, discharge placement and too early discharge. Conclusions Our findings demonstrate how important social service workers are in providing information to patients about different discharge options. The newness of SwissDRG and ATC is still likely to cause longer discussion times and, consequently, more workload for social service workers. Only a small fraction of patients disagreed with their place of discharge, mostly due to financial reasons.